2013
DOI: 10.4081/ijas.2013.e69
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Carcass and Meat Quality of Casertana, Italian Large White and Duroc x (Landrace x Italian Large White) Pigs Reared Outdoors

Abstract: To compare growth, skeletal development, carcass traits and meat quality of different genotypes, 10 Casertana (CT), 10 Italian Large White (LW) and 10 Duroc x (Landrace x Italian Large White) (DU) crosses, barrows of 90 days of age, were allotted to the same outdoor rearing and feeding conditions. Live weight was recorded and average daily gain (ADG) was calculated. At slaughter (330-day-old) dressing and lean percentages were determined; backfat thickness and loin eye depth were measured. Carcasses were disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 54 publications
7
13
2
Order By: Relevance
“…It is also in agreement with the results reported for IMF proportion (Labroue et al, 2000) or marbling density (Alfonso et al, 2005) in this breed, and confirms the great potential of local pig breeds for IMF deposition (Lebret, 2008;Pugliese and Sirtori, 2012). In agreement with the present results, lower LM collagen concentrations and higher proportion of non-reducible, thermo-resistant collagen cross-links were found in local Casertana compared with LW pigs at 330 days of age (Maiorano et al, 2013). Altogether, this indicates a lower muscle collagen concentration in local than in conventional breeds, despite a smaller loin eye area (personal data), suggesting a lower 'dilution rate' of collagen by muscle fibres in the local breeds, when compared at the same BW and also at the same age.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is also in agreement with the results reported for IMF proportion (Labroue et al, 2000) or marbling density (Alfonso et al, 2005) in this breed, and confirms the great potential of local pig breeds for IMF deposition (Lebret, 2008;Pugliese and Sirtori, 2012). In agreement with the present results, lower LM collagen concentrations and higher proportion of non-reducible, thermo-resistant collagen cross-links were found in local Casertana compared with LW pigs at 330 days of age (Maiorano et al, 2013). Altogether, this indicates a lower muscle collagen concentration in local than in conventional breeds, despite a smaller loin eye area (personal data), suggesting a lower 'dilution rate' of collagen by muscle fibres in the local breeds, when compared at the same BW and also at the same age.…”
Section: Resultssupporting
confidence: 93%
“…Accordingly, higher pHu and redness and lower lightness and drip loss were found in the loin from other local breeds compared with the LW pigs (e.g. Labroue et al, 2000 in Gascon andMaiorano et al, 2013 in Casertana pigs).…”
Section: Meat Quality Indicatorsmentioning
confidence: 87%
“…No information is available from current literature on the effect of sex or hatch on IMC properties in quails. Differences in collagen content and maturity between the sex of animals, attributed to hormonal effect, has been reported in findings on pork, beef, lamb, and deer (reviewed in Maiorano et al, 2013). However, the question of sex differences in terms of IMC seems to vary with species.…”
Section: Imc Propertiesmentioning
confidence: 92%
“…In contrast, Alvarado et al (2005) found that outdoor access resulted in higher pH. Nevertheless, literature often reported that meat from poultry (Ponte et al 2008) and pigs (Maiorano et al 2013) reared on outdoor access is characterized by lower pH indicating more glycogen in the muscle at slaughter, which then results in more lactate in the post-mortem process (Bonneau and Lebret 2010). However, the pH u values (ranging from 5.63-5.76) observed in this study varied within the pH range accepted for commercial meats.…”
Section: Physicochemical Properties and Fibre Diametermentioning
confidence: 94%